Neuromuscular Junction Disorders. Issue 5 (19th March 2013) - Liang, Chiawen Lucy; Han, Steve
Abstract : Abstract: Disorders of the neuromuscular junction, such as myasthenia gravis and Lambert‐Eaton myasthenic syndrome, constitute an important and treatable class of diseases. Both disorders are typically caused by an immunologically mediated attack on discrete components of the neuromuscular junction, compromise the efficacy of neurotransmitter transmission, and produce clinically distinct syndromes of fatigable muscle weakness. Although the history, clinical examination, and routine antibody testing can be diagnostic in many cases, specialized neurophysiological tests, such as repetitive nerve stimulation and single‐fiber electromyography, are essential tools in the diagnostic evaluation of patients with more complicated or atypical conditions. In this review, we introduce primary disorders of the neuromuscular junction, and discuss the salient clinical and laboratory workup appropriate for recognizing these disorders, and the typical findings seen on electrodiagnostic testing with repetitive nerve stimulation and single‐fiber electromyography.